The Secret of The Alchemist - Maxmudjonova Nargiza (Global Scientific Publishing, 2024)
In this article, the book „The Alchemist” is tried to analyze thoroughly by exploring some characters, symbols and signs and comparing some similarities with „The Language of Bird” („Lison ut-tayr”).
Keywords: symbols; Narcissus; being a priest; symbolic teachers